Supply potential and annual availability of timber and forest biomass resources for energy considering inter-prefectural trade in Japan. (September 2020) - Battuvshin, Biligt; Matsuoka, Yusuke; Shirasawa, Hiroaki; Toyama, Keisuke; Hayashi, Uichi; Aruga, Kazuhiro
Highlights: Timber and forest biomass resource availability estimated with inter-prefectural trade. Appropriate harvesting system determined based on topography. CTL has highest productivity and lowest cost; annual availability is highest under CTL. Thinning and additional regeneration subsidies enhance availability. Subsidy plays an important role in the supply of timber and forest biomass resources. Abstract: This study estimates the supply potential and annual availability of timber and forest biomass resources under profitable forest management in Japan. It focuses on four prefectures, namely, Fukushima, Ibaraki, Tochigi, and Gunma, and considers the trade between these prefectures. Production forests were extracted as subcompartments where the expected revenues surpassed all costs, from planting to final harvest. To estimate harvesting costs, appropriate harvesting systems were determined according to each prefecture's topographical features. The log markets and woody biomass power generation plants were assumed to be the destinations for timber and forest biomass resources. Annual availability from the Cut-To-Length (CTL) system, consisting of the use of harvesters and forwarders, accounted for 58 % of the total availability, even though the supply potential from CTL was only 15 %; this is because CTL is the most productive and least expensive harvesting system. Then, the effects of subsidies on availability are examined. Availability under an additional regeneration subsidy meets almost the entire current demand in this region. Furthermore, availability with a thinning subsidy can meet the forecasted future demand in this region, while availability with both thinning and additional regeneration subsidies can meet future demand in all prefectures analyzed in the present study. Thus, subsidies play an important role in the profitability of forestry operations as well as the supply of timber and forest biomass resources in Japan.